Serum Beta- 2 Microglobulin is a Reliable Biomarker to Predict Diabetic Nephropathy - M, Kamal; SA, Apu; A, kamal; I, Alam; AM, kamal; AKMS, Rahman (Archives of Clinical and Biomedical Research, 2021)
Background: Diabetic nephropathy (DN) is the major microvascular complication and leading cause of chronic kidney disease (CKD) globally. Early detection of diabetic nephropathy is necessary. Objective: To evaluate the serum beta-2 (β2) microglobulin as a biomarker to predict diabetic nephropathy. Methods: This study was conducted from March 2020 to February 2021 at Department of Laboratory Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. A total of 60 patients with type-2 diabetes mellitus (DM) were enrolled purposively. Among them, 30 patients had diabetic nephropathy (group I) and 30 were without diabetic nephropathy (group II). Their random blood sugar (RBS), serum creatinine, estimated glomerular filtration rate (e-GFR), serum beta- 2 (β2) microglobulin and urinary microalbumin levels were measured. Data were analyzed and compared by statistical tests. Results: Most of the patients in nephropathy group were male who belonged to 51 - 60 years age group and their mean e-GFR was significantly decreased (p<0.001). The mean serum β2 microglobulin level was significantly higher in patients with diabetic nephropathy (6.72 ± 2.032 μg/ml versus 3.44 ± 1.12 μg/ml, p<0.001). There was significant positive correlation between serum β2 microglobulin with serum creatinine (r=+0.549, p=0.002) and with urinary microalbumin (r=0.755, p<0.001), but a significant negative correlation with e-GFR (r=-0.627, p<0.001) in group I. The best cut-off point of serum β2 microglobulin for diabetic nephropathy was 4.35 μg/ml with 93.3% sensitivity and 80.0% specificity. Conclusions: Serum beta-2 (β2) microglobulin level is significantly high in diabetic nephropathy. Serum β2 microglobulin may be used as a reliable biomarker to predict diabetic nephropathy.